15 lessons on personal success. (FTPress Delivers, 2011)
"Proven techniques for defining your vision, building your credibility, motivating your team, handling surprises and failure, getting answers, finding your passion, living your dream, preserving your integrity, and achieving breakthrough personal performance! A brand new collection of essential insights for your business and career from world-renowned experts"--Resource description page.